Поразка Болгарії у Першій світовій війні в оцінках Народно-ліберальної ("стамболовістської") партії - Миколенко, Д. (Сiверянський лiтопис, 2019)
У статті розглядаються інтерпретації Народно-ліберальною партією Болгарії
поразки країни у Першій світовій війні. Автор підкреслює спроби представників двох
угруповань зазначеної політичної сили – «генадієвістів» і «петковістів» – виправдатися в очах громадськості шляхом перекладання провини за воєнну невдачу і її наслідки
на плечі царя Фердинанда І Кобурга. The article deals with the People’s Liberal Party of Bulgaria and its interpretations of the
country defeat in the First World War. The author points out that the representatives of both
political groups – “Genadiists” and “Petkovists” – tried to restore public confidence by shifting
the blame for military failure and its consequences on King Ferdinand I Coburg. The paper
also focuses on the attempts of supporters of the PLP leader (Nikola Genadiev) and the Party
Central Bureau Secretary (Dobri Petkov) to demonstrate the lack of any alternative to their
foreign policy concepts on the eve and during the global armed conflict in order to offer new
avenues for Sofia’s international course in the post-war world. However, the majority of the
country’s population regarded the “stambolovists” as the one of perpetrators of the military
catastrophe in 1918. Thus, they were unable to regain their lost positions and take one of the
significant places on the political scene of Bulgaria.